1991
DOI: 10.1128/jb.173.11.3419-3424.1991
|View full text |Cite
|
Sign up to set email alerts
|

Escherichia coli Fpg protein and UvrABC endonuclease repair DNA damage induced by methylene blue plus visible light in vivo and in vitro

Abstract: pBR322 plasmid DNA was treated with methylene blue plus visible light (MB-light) and tested for transformation efficiency in Escherichia coli mutants defective in either formamidopyrimidine-DNA glycosylase (Fpg protein) and/or UvrABC endonuclease. The survival of pBR322 DNA treated with MB-light was not significantly reduced when transformed into either fpg-1 or uvrA single mutants compared with that in the wild-type strain. In contrast, the survival of MB-light-treated pBR322 DNA was greatly reduced in the fp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
61
0
2

Year Published

1995
1995
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(68 citation statements)
references
References 47 publications
5
61
0
2
Order By: Relevance
“…Fpg primarily removes oxidized purines, whereas Nei and Nth primarily remove oxidized pyrimidines. We generated a substrate for Fpg by treating λ DNA with methylene blue (MB) plus visible light (24)(25)(26). Treatment of DNA with MB results not only in the formation of 8-oxoG but primarily its further oxidation products such as spiroiminodihydantoin (27,28), which are also recognized by Fpg (29).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fpg primarily removes oxidized purines, whereas Nei and Nth primarily remove oxidized pyrimidines. We generated a substrate for Fpg by treating λ DNA with methylene blue (MB) plus visible light (24)(25)(26). Treatment of DNA with MB results not only in the formation of 8-oxoG but primarily its further oxidation products such as spiroiminodihydantoin (27,28), which are also recognized by Fpg (29).…”
Section: Resultsmentioning
confidence: 99%
“…Single-molecule experiments were performed using λ DNA (New England BioLabs). λ DNA containing Tg or oxidized purine was generated by exposure to osmium tetroxide (OsO 4 ) plus heat and MB plus visible light, respectively, as previously described (24)(25)(26)(30)(31)(32). Briefly, 100 μg/mL λ DNA was treated with 0.2 and 1 μg/mL MB and then illuminated for 60 min with one 100-W lamp (Reveal; 100 W; 1,352 Lumens; A-19 Shape; General Electric) that was placed at a distance of 20 cm from the surface of a thinly coated 10-cm plate containing the DNA solution placed on ice.…”
Section: Methodsmentioning
confidence: 99%
“…Guanines are especially susceptible to modification by the reactive oxygen species, yielding mainly 8-oxoguanine, which results in GC-to-TA transversion mutagenesis (9). Several reports have indicated that the primary repair of 8-oxoG is performed by BER (6,10,35,40). Because oxidative stress represents a significant challenge to anaerobes such as P. gin- givalis, it is imperative that this organism develop mechanisms of oxidative stress resistance that will allow for persistence in the inflammatory condition of periodontitis.…”
Section: -Oxog Removal Activity In Other Anaerobesmentioning
confidence: 99%
“…The other strains showed no visible growth defect even at the higher dose of 60 J m 22 . Based on earlier studies in other organisms (Czeczot et al, 1991;Scott et al, 1999;Huang et al, 2006), it was not unexpected that the deficiency of Ung and Fpg did not result in any increased sensitivity of M. smegmatis to UV C radiation. However, these observations highlight that the NER pathway provides the major means to protect M. smegmatis against DNA damage caused by UV radiation.…”
Section: Analysis Of Uv Sensitivitymentioning
confidence: 99%